Does Pyrrhonism Have Practical or Epistemic Value? - Machuca, Diego Emanuel (2019)
My purpose in this paper is to examine whether Pyrrhonian scepticism, as this stance is described in Sextus Empiricus?s extant works, has practical or epistemic value. More precisely, I would like to consider whether the Pyrrhonist?s suspension of judgment (epochē) and undisturbedness (ataraxia) can be deemed to be of practical or epistemic value. By ?practical? value I mean both moral value and prudential value. Moral value refers to moral rightness and wrongness; prudential value to personal or social well-being. Hence, when I ask whether the Pyrrhonist?s suspension and undisturbedness have practical value, I mean whether they make us behave in a manner that is morally right or wrong, and whether they allow us to attain those goals that would make it possible to live well. As for ?epistemic? value, it refers basically to the values of attaining truth and avoiding error. Hence, when I ask whether the Pyrrhonist?s suspension has epistemic value, I mean whether it allows us to attain truth and avoid error. My main focus will be the practical value of both suspension and undisturbedness because this is the value on which ancient philosophy scholars critical of Pyrrhonism have laid emphasis. The reason for examining the epistemic value of suspension is that doing so will enable a fuller assessment of the significance of Pyrrhonism as a kind of philosophy, which is my primary concern.